Formulation ancl Evaluation of a Topical Antioxidant Preparation - Ahmed Hassan, Hassan; Muthana Yousif, Emad; Ahmed Yas, Ali (Tikrit Journal of Pharmaceutical Sciences, 2023)
The aim of this work was to prepare the stable vitamin C rvater/oilirvater (w/o/w) multiple emulsions, to investigate the usage of poloxamine 908, to observe the influence of surfactant percentage on the properties of multiple emulsions. Multiple emulsions were prepared by liquid paraffin, cetyl dimethicone copolyol and poloxamine 908 by a two - step emulsification procedure. Vitamin C r,vas used as an antioxidant and r,vater - soluble model. The viscosity, conductivity and globule size of multiple emulsions rvere follor,ved over time. The formulations containing 1o/o cetyl dimethicone copolyol and I or Zoh poloxamine 908 lvere the most stable systems. The globule size of multiple emulsions ranged from 20 to 37 pm and did not change during time. The yield of multiple en-rulsions rvas betrveen 99.6Yo and 98.7o/o. The conductivity increased and the viscosity of systems decreased during time. Increase in poloxamine 908 influenced the viscosity of the system, rvith the viscosity decreasing as the hydrophitic surfactant concentrations were increased. Vitamin C rclease lronr the multiple emulsions u'as slow'; the release rvas aft'ccted by both surlactant concentratior.rs. Poloxanrirre 908 could be used as a hydrophilic surfactant for formulation of rv/o/rv multiple emulsions. The concentration of poloxanrine 908 was a very important parameter in preparing stable multiple enrulsions. It 'uvas concluded that vitamin C might be transported out by molecular diffusion and through a reverse micellar mechanism controlled by the viscosity of the system